Effect of age on treatment outcomes in Clostridium difficile infection. - Louie, T; Miller, M; Crook, D; Lentnek, A; Bernard, L; High, K; Shue, Y; Gorbach, S (2013)
OBJECTIVES: To determine the effect of advancing age on the clinical outcomes of Clostridium difficile (CDI) treatment. DESIGN: Regression modeling of results from two double-blind randomized multicenter studies on the treatment of primary and first recurrent cases of CDI to examine for effects of age and study drug on outcomes of cure (resolution of diarrhea), recurrence within 4 weeks of completing successful therapy, and cure without recurrence. SETTING: Participants were randomized into studies in the United States, Canada, and Europe. PARTICIPANTS: Nine hundred ninety-nine individuals with toxin-positive CDI were randomized to receive vancomycin (125 mg 4 times daily) or fidaxomicin (200 mg twice daily) for 10 days. MEASUREMENTS: The effect of advancing age in those aged 18 to 40 years and in 10-year increments thereafter was examined. RESULTS: The model predicts a 17% lower clinical cure, 17% greater recurrence, and 13% lower sustained clinical response by advancing decade than in those younger than 40 (P < .01 each). Clinical cure was similar in the fidaxomicin and vancomycin treatment groups, although fidaxomicin was associated with a more than 50% lower relative risk for recurrence than vancomycin (P < .001). Multivariate regression modeling showed that risk factors accounting for poorer outcomes with advancing age include infection with the BI strain type, inpatient status, renal insufficiency, leukocytosis, hypoalbuminemia, and concomitant medication exposure. CONCLUSION: Measurable and progressive deterioration in CDI treatment outcomes occurred with advancing age in those aged 40 and older, highlighting the need for prevention and treatment strategies. Fidaxomicin treatment was associated with a 60% lower risk of recurrence than vancomycin after adjusting for age, concomitant antibiotics, and C. difficile strain.